2011
DOI: 10.3141/2213-04
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Trip and Roadway Characteristics to Manage Safety in Traffic Analysis Zones

Abstract: A transportation network is a conglomeration of road-traffic-environment modules and features multicategories of interdependent factors. This mix makes the management of safety in traffic analysis zones (TAZs) explicitly challenging. This study investigated the association between crash frequencies and various types of trip productions and attractions in combination with the road characteristics of 1,349 TAZs of four counties in the state of Florida. Crash safety management of these TAZs is emphasized through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(50 citation statements)
references
References 17 publications
4
45
1
Order By: Relevance
“…One of the main objectives of macro-level crash prediction analysis is to explain observed cross-sectional variations in safety using zone-level covariates at different spatial scales (e.g., states, counties, traffic analysis zones, and census wards) (Washington et al, 2006;Quddus 2008;. These macro-level CPMs may aid transportation agencies in more effectively incorporating safety consideration into transportation planning and management (Abdel-Aty et al, 2011;Huang et al, 2013;Xu and Huang, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…One of the main objectives of macro-level crash prediction analysis is to explain observed cross-sectional variations in safety using zone-level covariates at different spatial scales (e.g., states, counties, traffic analysis zones, and census wards) (Washington et al, 2006;Quddus 2008;. These macro-level CPMs may aid transportation agencies in more effectively incorporating safety consideration into transportation planning and management (Abdel-Aty et al, 2011;Huang et al, 2013;Xu and Huang, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…Hadayeghi et al 2010a, 2010b, Lovegrove 2005 or NOTs (e.g. Abdel-Aty et al 2011a, 2011b, Naderan and Shahi 2010 and NOCs per TAZ. The only exception was observed where VKT on motorways was negatively associated with "Car-Slowmode" crashes.…”
Section: Model Developmentmentioning
confidence: 99%
“…Reviewing the literature for different model forms showed that the following model has been widely used in different studies (Abdel-Aty et al, 2011;Hadayeghi, 2009;Lovegrove, 2005):…”
Section: Generalized Linear Modelmentioning
confidence: 99%
“…ZCPMs have been initially introduced by Levine et al based on Linear Regression models (Levine et al 1995a). However, the most common modeling framework for ZCPMs is the Generalized Linear Modeling (GLM) framework (Abdel-Aty et al, 2011;Aguero-Valverde and Jovanis, 2006;Hadayeghi et al, 2010Hadayeghi et al, , 2007Hadayeghi et al, , 2003; Khondakar et al, 2010;Lord and Mannering, 2010;Lovegrove andSayed, 2007, 2006;Lovegrove et al, 2010;Lovegrove and Litman, 2008;Naderan and Shahi, 2010;Pirdavani et al, 2013). Within a GLM framework, fixed coefficient estimates explain the association between the dependent variable and the explanatory variables.…”
Section: Introductionmentioning
confidence: 99%